Spatial distribution of the coffee-leaf-miner (Leucoptera coffeella) in an organic coffee (Coffea arabica L.) field in formation - Scalon, João Domingos; Alves, Gabriella de Freitas; Avelar, Maria Betania Lopes; Zacarias, Mauricio Sérgio (Coffee Science - ISSN 1984-3909, 2011)
Coffee production has been one of the economy pillars of many tropical countries. Unfortunately, this crop is susceptible to infestation by the coffee-leaf-miner (Leucoptera coffeella (Guérin-Mèneville & Perrottet, 1842)) which causes severe damage to coffee plantations with losses that may reach 80% of the total production. In recent years, researchers have been trying to develop practices for minimizing the use of pesticides in the coffee-leaf-miner control. It is well known that the understanding of the spatial distribution of insects may be important in the context of biological control of pests. The aim of this work is to use spatial statistical methods for characterizing the spatial distribution of the coffee-leaf-miner in a plantation of organic coffee (Coffea arabica L.). This work uses the number of mined leaves taken from a grid of 35 sampling locations from one hectare of an organic plantation of coffee in the second year of its implantation during the annual peak population (September 2006) of the coffee-leaf-miner. A geostatistical method (semivariogram) was used to characterize the spatial variability of the coffee-leaf-miner in an organic coffee field in formation. The results showed that the coffee-leaf-miner population was randomly distributed in the field during the annual peak population.